Enhancing the Communication Bandwidth of FH-MIMO DFRC Systems Through Constellation Rotation Modulation - Jiangtao Liu; Weibin Jiang; Wentie Yang; Tao Su; Jianzhong Chen (Remote Sensing)
This paper presents a technique based on Constellation Rotation Modulation (CRM) to enhance the communication bandwidth of Frequency-Hopping Multiple-Input Multiple-Output Dual-Function Radar and Communication (FH-MIMO DFRC) systems. The technique introduces the dimension of constellation diagram rotation without increasing the system bandwidth or power consumption, significantly improving communication efficiency. Specifically, CRM, by rotating the constellation diagram, combines with traditional Frequency-Hopping Code Selection (FHCS) and Quadrature Amplitude Modulation (QAM) to achieve higher data transmission rates. Through theoretical analysis and experimental verification, we demonstrate the specific modulation and demodulation principles of CRM, and we compare the differences between the minimum Euclidean distance-based and constellation diagram folding projection fast demodulation methods. The impact of the proposed modulation on radar detection range and detection performance was analyzed in conjunction with radar equations and ambiguity functions. Finally, achieved through simulation analysis of radar and communication systems, as well as actual system testing on an SDR platform, the simulation and experimental results indicate that CRM modulation can significantly enhance communication bandwidth while maintaining radar detection performance, thereby validating the accuracy and reliability of the theory.